LO13: Characteristics of emergency department visits by community-dwelling older adults who screened positive for elder abuse during home care assessments. (May 2019) - Mercier, E.; Jones, A.; Brousseau, A.; Hirdes, J.; Mowbray, F.; Emond, M.; Melady, D.; Costa, A.
Abstract : Introduction : Elder abuse is infrequently detected in the emergency department (ED) and less than 2% are reported to proper law authorities by ED physicians. This study aims to examine the characteristics of community-dwelling older adults who screened positive for elder abuse during home care assessments and the epidemiology of ED visits by these patients relative to other home care patients.Methods : This study utilized a population-based retrospective cohort study of home care patients in Canada between April 1, 2007 and March 31, 2015. Standardized, comprehensive home care assessments were extracted from the Home Care Reporting System. A positive screen for elder abuse was defined as at least one these criteria: fearful of a caregiver; unusually poor hygiene; unexplained injuries; or neglected, abused, or mistreated. Home care assessments were linked to the National Ambulatory Care Reporting System in the regions and time periods in which population-based estimates could be obtained to identify all ED visits within 6 months of the home care assessment.Results : A total of 30, 413 from the 2, 401, 492 patients (1.3%) screened positive for elder abuse during a home care assessment. They were more likely to be male (40.5% versus 35.3%, p < 0.001), to have a cognitive impairment (82.9% versus 65.3%, p < 0.001), a higher frailty index (0.27 versus 0.22, p < 0.001) and to exhibit more depressive symptoms (depression rating scale 1 or more: 68.7% versus 42.7%, p < 0.001). Patient who screened positive for elder abuse were less likely to be independent in activities of daily living (41.9% versus 52.7%, p < 0.001) and reported having fallen more frequently (44.2% versus 35.5%, p < 0.001). Caregiver expressing distress was associated with elder abuse (35.3% versus 18.3%, p < 0.001) but not a higher number of hours caring for the patient. Victims of elder abuse were more likely to attend the ED for low acuity conditions (Canadian triage and acuity scale (CTAS) 4 or 5). Diagnosis at discharge from ED were similar with the exception of acute intoxication that was more frequent in patients who are victims of abuse.Conclusion : Elder abuse is infrequently detected during home care assessments in community-dwelling older adults. Higher frailty index, cognitive impairment, depressive symptoms were associated with elder abuse during homecare assessments. Patients who are victims of elder abuse are attending EDs more frequently for low acuity conditions but ED diagnosis at discharge, except for acute intoxication, are similar.